(untitled) (Ameghiniana, 2024)
One of the most endemic Lower Devonian fauna in the Central Andean basin of Western Gondwana is the association of brachiopods characterized by the terebratulid Scaphiocoelia boliviensis. This benthic association is analyzed in seven localities in the strike and the dip of the basin (Ayo Ayo, belén, Candelaria-Icla, El Peral-Presto, Sobo Sobo, Sella, and Abra de Zenta) integrating several ages based on palynomorphs, mainly chitinozoans, that have been published in the last 20 years. The Scaphiocoelia biofacies is defined from the statistical treatment of 31 associated taxa in seven columns of Pragian age. In addition, the most frequent facies enclosing the biofacies are discussed. The result of this integration postulates habitat tracking as a migration strategy for the biofacies, following the basic pattern of Walther’s law. Likewise, the Scaphiocoelia biofacies responds to the sea level fluctuations in a regressive-transgressive cycle, with an important development in the maximum regression surface, the falling stage-lowstand systems tracts and in some fine-grained sandstones of progradations in the highstand systems tract. At the beginning of the transgression, the Scaphiocoelia biofacies keep its composition in fine sandstone beds but disappear before the maximum flooding and poorly oxygenated levels. The diachronic character of this biofacies is stressed when correlations in the basin and between basins are made.